2004
DOI: 10.1134/1.1795947
|View full text |Cite
|
Sign up to set email alerts
|

NGC 7468: A galaxy with an inner polar disk

Abstract: Abstract. We present our spectroscopic observations of the galaxy NGC 7468 performed at the 6-m Special Astrophysical Observatory telescope using the UAGS long-slit spectrograph, the multipupil fiber spectrograph MPFS, and the scanning Fabry-Perot interferometer (IFP). We found no significant deviations from the circular rotation of the galactic disk in the velocity field in the regions of brightness excess along the major axis of the galaxy (the putative polar ring). Thus, these features are either tidal stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Our coarse spatial resolution does not allow us to either confirm or disprove the existence of this inner disk, but the kinematics of the main disk agree well with the data shown by Shalyapina et al (2004): see for instance the peak in the velocity profile at 30 south of the nucleus, and then the sharp decrease (their Fig. 2a).…”
Section: Mrk 314 (= Ngc 7468)mentioning
confidence: 51%
See 1 more Smart Citation
“…Our coarse spatial resolution does not allow us to either confirm or disprove the existence of this inner disk, but the kinematics of the main disk agree well with the data shown by Shalyapina et al (2004): see for instance the peak in the velocity profile at 30 south of the nucleus, and then the sharp decrease (their Fig. 2a).…”
Section: Mrk 314 (= Ngc 7468)mentioning
confidence: 51%
“…An extensively kinematic analysis of this galaxy has been performed by Shalyapina et al (2004), who found that Mrk 314 harbors two kinematics subsystems of ionized gas: the main gaseous disk, and a smaller inner disk oriented orthogonally to it. Our coarse spatial resolution does not allow us to either confirm or disprove the existence of this inner disk, but the kinematics of the main disk agree well with the data shown by Shalyapina et al (2004): see for instance the peak in the velocity profile at 30 south of the nucleus, and then the sharp decrease (their Fig.…”
Section: Mrk 314 (= Ngc 7468)mentioning
confidence: 99%
“…However, a possible fraction of polar structures among BCD galaxies seems to be larger (up to 10-15%). For instance, 5 galaxies out of 28 nearby luminous BCDG in the sample by Cairós et al [12] possess polar structures: Mrk 33, Mrk 370, Mrk 314 [13], II Zw 71 [14] and III Zw 102 [15]. Therefore the current burst of star formation in these galaxies can be connect with the same interaction event (accretion or merging) which also transported gas clouds on polar orbits.…”
Section: Discussionmentioning
confidence: 99%
“…Shalyapina et al (2004), who interpret it as the superposition of two kinematic subsystems of ionized gas.…”
Section: Mrk 314mentioning
confidence: 99%